2017
DOI: 10.7575/aiac.ijalel.v.6n.4p.163
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Language Learning Motivation of Saudi Military Cadets

Abstract: Using Dörnyei’s  (2009) L2 Motivational Self System as the main theoretical framework, this paper reports a study of Saudi military cadets’ motivation to learn English. The study aimed to: a) investigate the usefulness of Dörnyei’s model for understanding and explaining English language motivation in this global context; b) capture other motivational factors seen to be relevant to the designated group’s motivation to learn English. A sample of 194 Saudi military cadets participated in the survey. Correlation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Similar to the IL2S, the third construct of the L2MSS (the L2LE) has a significant impact on the learning effort of L2 students. The results of a number of studies reveal an even stronger impact (Alqahtani, 2017b;Csizér & Kormos, 2009;Islam, Lamb, & Chambers, 2013). The L2LE has been referred to using a number of terms interchangeably; for example, "Language Learning Attitudes" (LLA) (Alqahtani, 2018a;2018b), "Attitudes to L2 Learning" (You, Dörnyei, & Csizér, 2016), "Attitudes to Learning English" (Islam et al, 2013), and "L2 Learning Attitude" (Csizér & Kormos, 2008b).…”
Section: The L2mssmentioning
confidence: 99%
“…Similar to the IL2S, the third construct of the L2MSS (the L2LE) has a significant impact on the learning effort of L2 students. The results of a number of studies reveal an even stronger impact (Alqahtani, 2017b;Csizér & Kormos, 2009;Islam, Lamb, & Chambers, 2013). The L2LE has been referred to using a number of terms interchangeably; for example, "Language Learning Attitudes" (LLA) (Alqahtani, 2018a;2018b), "Attitudes to L2 Learning" (You, Dörnyei, & Csizér, 2016), "Attitudes to Learning English" (Islam et al, 2013), and "L2 Learning Attitude" (Csizér & Kormos, 2008b).…”
Section: The L2mssmentioning
confidence: 99%
“…In a previous study, Kormos & Csizér (2007) found that Hungarian L2 learners received help and encouragement from their parents regardless of their parents' ability to speak English on the basis of their belief in the importance that acquiring English had for their children. Parents' influence on their children's L2 motivation is even stronger in Asian and Arab cultures, as previous L2 motivation studies have revealed (Alqahtani, 2015(Alqahtani, , 2017Islam et al, 2013;Lamb, 2012;Taguchi et al, 2009).…”
Section: Parental Encouragementmentioning
confidence: 63%
“…Like the Ideal L2 Self, the L2 Learning Experience has been found to have a significant impact on learners' L2 learning effort. In some studies, the L2 Learning Experience was found to contribute more than the Ideal L2 Self to learners' L2 learning effort (Alqahtani, 2015(Alqahtani, , 2017Csizér & Kormos, 2009;Islam et al, 2013;Lamb, 2012). Previous studies have used various terms interchangeably to refer to this construct of the L2 Motivational Self System or to part of it; for example, "Language Learning Attitudes" (Alqahtani, 2015(Alqahtani, , 2017, "Attitudes to L2 Learning" (You et al, 2016), "Attitudes to Learning English" (Islam et al, 2013;Taguchi et al, 2009), and "L2 Learning Attitude" (Kormos et al, 2011).…”
Section: The L2 Motivational Self Systemmentioning
confidence: 99%
See 2 more Smart Citations